2014
DOI: 10.1016/j.crohns.2014.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave and disability pension in inflammatory bowel disease: A systematic review

Abstract: Inflammatory bowel disease patients experience a high burden in work-related outcomes. Additional data on productivity losses and the long-term impact of interventions is needed to help inform decision-makers about treatment options and their benefits in reducing productivity losses in inflammatory bowel disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
44
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 62 publications
3
44
1
4
Order By: Relevance
“…Persons with IBD are more likely to be unemployed compared to the general population [4]. This could in part be explained by a lack of workplace coping strategies available to those with IBD and a lack of understanding of employers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons with IBD are more likely to be unemployed compared to the general population [4]. This could in part be explained by a lack of workplace coping strategies available to those with IBD and a lack of understanding of employers.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has been undertaken on the impact of IBD on work-related outcomes, and most studies report that persons with IBD experience a high burden in work-related outcomes because of an increased frequency of sick leave, disability pension, and unemployment [4-6]. To measure health-related work productivity loss among patients, many studies use the Work Productivity Activity Impairment Questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment regimens requiring multiple daily dosing can interfere with patients' daily life, negatively affecting adherence to therapy and leading to poorer long-term outcomes in UC [24]. Biologics have the potential to improve HRQoL [25].With regard to the workplace, UC is associated with increases of up to 88% in absenteeism, 69% for sick leave, 66% for reduced capacity, 50% for unemployment and 19% for disability pension -with the risk for receiving a disability pension highest in the 18-39-year age group [26,27]. Moreover, many patients undergoing colectomy persistently have work disability after the surgery, possibly due to long-term postoperative complications [27].…”
mentioning
confidence: 99%
“…Moreover, many patients undergoing colectomy persistently have work disability after the surgery, possibly due to long-term postoperative complications [27]. On the other hand, biologic agents have shown positive effects on improving absenteeism and presenteeism at work [26]. In a recent meta-analysis of randomised trials data, the TNF inhibitors infliximab and adalimumab were more effective than placebo in reducing the rate of UCrelated hospitalisation, whereas treatment with infliximab (but not adalimumab or golimumab) was associated with a reduced rate of colectomy at 54 weeks [28].…”
mentioning
confidence: 99%
“…Almost the same number of people said that IBD had hindered them in their personal life and relationships (51). One consequence of IBD is a reduced ability to work or study (54,55). A tenyear follow-up study showed that an increased risk for disability pension was associated with being diagnosed at a young age (under 30 years of age at the time of diagnosis), steroid treatment one year after diagnosis, colectomy during the first year and more than two relapses during the first year (56).…”
Section: Impact On Life Situationmentioning
confidence: 99%